Businesses' voluntary pro-health tobacco policies: a review and research agenda. Issue 1 (26th September 2011) - McDaniel, Patricia A; Malone, Ruth E
Abstract : Research on the role of businesses in tobacco control has focused primarily on retailers, advertising firms and the hospitality industry, all of which have tended to support tobacco industry interests and resist effective tobacco control policies. However, in several countries, businesses have a history of voluntarily adopting tobacco-related policies that may advance tobacco control objectives. These phenomena have received little research attention. Existing literature on businesses ending tobacco sales, instituting voluntary workplace smoking restrictions and establishing non-smoker only hiring policies was reviewed. A research agenda on voluntary business initiatives would enhance and complement research on mandatory tobacco control policies by identifying new advocacy opportunities; suggesting avenues for strengthening or reinforcing existing policy initiatives; laying the groundwork for new mandatory policies; helping to inform ethical debates about contentious voluntary policies; and contributing to a better understanding of how alliances between the tobacco industry and other businesses might be weakened.